Feeding Strategies for Sheep on Java, Result from On-Station and On-Farm Research - I Gede Suparta Budisatria; J. B. Schiere; E. Baliarti (Buletin Peternakan, 2007)
File lengkap ada dalam bentuk PDF dibawah ini